River inundation suggests ice-sheet runoff retention. Issue 228 (2015) - Overeem, Irina; Hudson, Benjamin; Welty, Ethan; Mikkelsen, Andreas; Bamber, Jonathan; Petersen, Dorthe; Lewinter, Adam; Hasholt, Bent
Abstract: The Greenland ice sheet is experiencing dramatic melt that is likely to continue with rapid Arctic warming. However, the proportion of meltwater stored before reaching the global ocean remains difficult to quantify. We use NASA MODIS surface reflectance data to estimate river discharge from two West Greenland rivers – the Watson River near Kangerlussuaq and the Naujat Kuat River near Nuuk – over the summers of 2000–12. By comparison with in situ river discharge observations, 'inundation–discharge' relations were constructed for both rivers. MODIS-based total annual discharges agree well with total discharge estimated from in situ observations (86% of summer discharge in 2009 to 96% in 2011 at the Watson River, and 106% of total discharge in 2011 to 104% in 2012 at the Naujat Kuat River). We find, however, that a time-lapse camera, deployed at the Watson River in summer 2012, better captures the variations in observed discharge, benefiting from fewer data gaps due to clouds. The MODIS-derived estimates indicate that summer discharge has not significantly increased over the last decade, despite a strong warming trend. Also, meltwater runoff estimates derived from the regional climate model RACMO2/GR for the drainage basins are higher than our reconstructions of river discharge. These results provide indirect evidence for a considerable component of water storage within the glacio-hydrological system.